The Impact of First-Line Anti-Tubercular Drugs’ Pharmacokinetics on Treatment Outcome: A Systematic Review - Sileshi T (Dove Medical Press, 2021)
Tesemma Sileshi,1,2 Esayas Tadesse,1 Eyasu Makonnen,2 Eleni Aklillu3 1Ambo University, Department of Pharmacy, Ambo, Ethiopia; 2Addis Ababa University, College of Health Sciences, Addis Ababa, Ethiopia; 3Karolinska Institutet, Department of Laboratory Medicine, Stockholm, SwedenCorrespondence: Tesemma SileshiAmbo University, P.O Box 19 Ambo University, Ambo, EthiopiaTel +251 911550975Email tesemmasileshi@gmail.comBackground: Tuberculosis remains the major public health problem besides tremendous efforts to combat it. Most tuberculosis patients are treated with a standard dose of first-line anti-TB drugs. The cure rate, however, varies from patient to patient. Various factors have been related to anti-TB treatment failure. In recent years, studies associating lower plasma concentrations of anti-TB drugs with poor treatment outcomes are emerging although the results are inconclusive.Objective: Investigate the impact of first-line anti-tubercular drugs pharmacokinetics on treatment outcome.Methods: A systematic search of Pubmed, EMBASE, Web of Science, and the Cochrane Library for articles published in the English language between January 2010 to June 2020 was conducted to identify eligible studies describing associations of first-line anti-tubercular drug pharmacokinetics with treatment outcomes. The primary outcomes considered were pharmacokinetics parameter results and its association with treatment outcome.Results: The search identified 1754 articles of which twelve articles; ten prospective observational studies and two controlled clinical trials fulfilled the eligibility criteria. The majority of the studies showed target concentrations for the first-line anti-tubercular drugs below the current standard range. Among the twelve studies, eleven studies assessed rifampicin pharmacokinetics of which eight reported association of drug concentration and treatment outcomes. Similarly, four out of eight and three out of seven reported drug concentration and treatment outcome association for isoniazid and pyrazinamide, respectively. Despite the low plasma concentration, a favorable treatment outcome was achieved for the bulk of the patients. Irrespective of the inconsistency, an increase in exposure to rifampicin improved the outcome, and lower rifampicin, isoniazid, and pyrazinamide concentration are associated with poor outcome. No data are available for ethambutol associating its pharmacokinetics with treatment outcomes.Conclusion: The pharmacokinetics of first-line antitubercular drugs can influence treatment outcomes. Further controlled clinical studies are, however, required to establish these relationships.Keywords: tuberculosis, pharmacokinetics, treatment outcomes, anti-TB drugs